Cryptogenic cholestasis in young and adults: ATP8B1, ABCB11, ABCB4, and TJP2 gene variants analysis by high-throughput sequencing - Vitale, Giovanni; Raimondi, Francesco; Russell, Robert B. (Journal of gastroenterology, 2018)
BackgroundMutations in ATP-transporters ATPB81, ABCB11, and ABCB4 are responsible for progressive familial intrahepatic cholestasis (PFIC) 1, 2 and 3, and recently the gene for tight junction protein-2 (TJP2) has been linked to PFIC4.AimAs these four genes have been poorly studied in young people and adults, we investigated them in this context here.MethodsIn patients with cryptogenic cholestasis, we analyzed the presence of mutations by high-throughput sequencing. Bioinformatics analyses were performed for mechanistic and functional predictions of their consequences on biomolecular interaction interfaces.ResultsOf 108 patients, 48 whose cause of cholestasis was not established were submitted to molecular analysis. Pathogenic/likely pathogenic mutations were found in ten (21%) probands for 13 mutations: two in ATP8B 1, six in ABCB11, two in ABCB4, three in TJP2. We also identified seven variants of uncertain significance: two in ATP8B1, one in ABCB11, two in ABCB4 and two in TJP2. Finally, we identified 11 benign/likely benign variants. Patients with pathogenic/likely pathogenic mutations had higher levels of liver stiffness (measured by FibroScan®) and bile acids, as well as higher rates of cholestatic histological features, compared to the patients without at least likely pathogenic mutations. The multivariate analysis showed that itching was the only independent factor associated with disease-causing mutations (OR 5.801, 95% CI 1.244-27.060, p = 0.025).ConclusionsMutations in the genes responsible for PFIC may be involved in both young and adults with cryptogenic cholestasis in a considerable number of cases, including in heterozygous status. Diagnosis should always be suspected, particularly in the presence of itching.